Role of psychological ownership and authenticity strength in the relationship between authentic leadership and sport team performance: A multilevel analysis. (September 2021) - Grégoire, Bosselut; Laure, Guibert; Sarah, Meyer; Séverine, Chevalier; Evelyne, Fouquereau
Abstract: Objectives: Understanding how and when authentic leadership (AL) is related to teams' performance is an important issue. The objective of the present study was to investigate the potential indirect role of psychological ownership (PO) in the relationship between AL and team sport performance for both athletes and coaches. We also hypothesized that AL perceived strength could moderate this relationship. Design and methods: 337 athletes (243 females) and their 44 coaches (3 females) completed questionnaires assessing AL and PO. Objective performance was assessed at the end of the season. Results: There was a link between players' perception of AL as exogenous variables and team performance as dependent variable via player's perception of PO. Coach's perception of PO did not affect the relationship between coach's perception of AL and team performance. Results did not suggest a moderating effect of AL perception strength. Conclusions: The current study provides the first evidence of relationship between AL and team performance through PO in team sports. However, this study did not support our hypothesis at the coach level. Theoretical and practical implications are discussed. Highlights: Psychological ownership mediated the relationship between leadership and performance at athlete level. No mediating relationship was found at coach level. Results did not suggest a moderating effect of leadership perception strength.